Comparative Study of the Antioxidant Status and Inflammatory Markers in Type 2 Diabetic Male and Female Nephropathy Subjects - Kafle, Deepak (International Journal of Pharmaceutical & Biological Archive, 2021)
Background: Diabetic nephropathy is one of the microvascular complications of Type2 diabetes mellitus (T2DM). Free radicals are formed disproportionately in diabetes by glucose oxidation, nonenzymatic glycation of proteins, and the subsequent oxidative degradation of glycated proteins. An abnormally high level of hyperglycemia generates reactive oxygen species (ROS) with simultaneous decline of antioxidant levels causing increased lipid peroxidation in T2DM leading microvascular complications. Aims and Objective: The study aimed to predict the development of diabetic nephropathy due to oxidative stress in type-2 male and female diabetic nephropathy subjects. Material and Methods: Serum levels of inflammatory markers (Interleukin-6 [IL-6] and Tumor necrosis factor alpha [Tnf-Î±]), antioxidants, [Glutathione reductase (GR) and Glutathione peroxidase (GPx)], plasma malondialdehyde (MDA), fasting blood sugar, urea and creatinine levels were estimated in controls (n=50, males and n=50, females) and T2DM with diabetic nephropathy ((n=50, males and n=50, females) and comparison was done. A Studentâ€™s t-test was used to estimate differences between the groups. All parameters were given as mean Â± standard deviation. The criterion for significance was P < 0.05. Conclusion: From our study, it was concluded that inflammatory markers, IL-6 and TNF-Î±, were found to be increased in type 2 female diabetic nephropathy subjects than male nephropathy subjects. Antioxidant Gpx enzyme levels are found to be decreased in the erythrocyte of both female diabetic nephropathy and male nephropathy subjects, however, decrease in Gpx level in female subjects was more than in male nephropathy subjects of type 2 diabetes.